Studies on Eupariini Schmidt, 1810 (Coleoptera: Scarabaeidae: Aphodiinae) with description of the new species of Ataenius Harold, 1867 and Saprosites Redtenbacher, 1857 - Minkina, Łukasz; Skelley, Paul (Zootaxa, 2025)
Two new species Eupariini Schmidt, 1810: Ataenius trox Minkina & Skelley, new species from Mato Grosso in Brasil and Saprosites halmaheiraensis Minkina & Skelley, new species from Halmahera Island in the Northern Moluccas, Indonesia are described and illustrated. The male of Airapus rudolphi Bellmann & Minkina, 2023 is described supplementarily; its aedeagus is presented for the first time, and the species is reported from Mentawai Islands, Indonesia for the first time.